2010
DOI: 10.3109/07357907.2010.512594
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-6, 7, or 9 Overexpression in the Human Gastric Adenocarcinoma Cell Line AGS Increases Its Invasiveness, Migration, and Proliferation Rate

Abstract: Altered claudin expression is related to metastatic potential, poor prognosis, or tumor recurrence. We analyzed if the overexpression of claudin-6, claudin-7, or claudin-9 in AGS cells altered cell motility, invasiveness, or proliferation rate. Claudin-7, claudin-9, and claudin-6 enhanced their invasive potential by 3.4-fold, 1.6-fold, and 2.0-fold, respectively. Claudin-6 and claudin-9 enhanced cell migration, while the proliferation rate of claudin-6-, claudin-7-, and claudin-9-transfected cells increased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 47 publications
3
59
2
Order By: Relevance
“…They also found that knockdown of claudin 1 increased the tumorigenicity of human gastric cancer cells (12). However, study also found that overexpression of other members of claudin (CLDN6, 7 and 9) in gastric cancer cells increased the invasiveness, migration and proliferation (37).…”
Section: Discussionmentioning
confidence: 95%
“…They also found that knockdown of claudin 1 increased the tumorigenicity of human gastric cancer cells (12). However, study also found that overexpression of other members of claudin (CLDN6, 7 and 9) in gastric cancer cells increased the invasiveness, migration and proliferation (37).…”
Section: Discussionmentioning
confidence: 95%
“…Cldn6, a member of the tight junction family, has been reported to play an important role during mouse embryonic epithelium formation [4] and the development of endodermal tissues [5]. The level of Cldn6 expression is correlated with dedifferentiation and malignant proliferation of epithelial cells [6,7]. However, little is known about the characteristics and function of Cldn6 in mouse PSCs [8].…”
Section: Dear Editormentioning
confidence: 99%
“…Increased expression of claudin-6, -7 and -9 is sufficient to enhance tumorigenic properties of a gastric adenocarcinoma cell line (Zavala-Zendejas et al, 2011). Claudin-1 is not expressed in the epithelium of normal canine colorectal mucosa, but increased expression of this protein was observed in canine low-grade colorectal adenocarcinoma (Jakab et al, 2010).…”
Section: Discussionmentioning
confidence: 99%